Cisplatin overcomes radiotherapy resistance in OCT4-expressing head and neck squamous cell carcinoma. (April 2022) - Routila, Johannes; Qiao, Xi; Weltner, Jere; Rantala, Juha K; Carpén, Timo; Hagström, Jaana; Mäkitie, Antti; Leivo, Ilmo; Ruuskanen, Miia; Söderlund, Jenni; Rintala, Marjut; Hietanen, Sakari; et al.
Highlights: OCT4 expression identifies HNSCCs that have increased radioresistance but respond to cisplatin. Low expression of OCT4 is linked to sensitivity to radiation therapy. OCT4 may be a key to de-escalation of HNSCC cancer therapy. The results were validated in four clinical datasets and ex vivo drug screening. Abstract: Objectives: Cisplatin is combined with radiotherapy for advanced head and neck squamous cell carcinoma (HNSCC). While providing a beneficial effect on survival, it also causes side effects and thus is an important target when considering treatment de-escalation. Currently, there are no biomarkers to predict its patient-selective therapeutic utility. In this study, we examined the role of the stem cell factor OCT4 as a potential biomarker to help clinicians stratify HNSCC patients between radiotherapy and chemoradiotherapy. Materials and methods: OCT4 immunohistochemical staining of a population-validated tissue microarray (PV-TMA) (n = 166) representative of a standard HNSCC patients was carried out, and 5-year survival was analyzed. The results were validated using ex vivo drug sensitivity analysis of HNSCC tumor samples, and further cross-validated in independent oropharyngeal (n = 118), nasopharyngeal (n = 170), and vulvar carcinoma (n = 95) clinical datasets. In vitro, genetically modified, patient-derived HNSCC cells were used. Results: OCT4 expression in HNSCC tumors was associated with radioresistance. However, combination therapy with cisplatin was found to overcome this radioresistance in OCT4-expressing HNSCC tumors. The results were validated by using several independent patient cohorts. Furthermore, CRISPRa-based OCT4 overexpression in the HNSCC cell line resulted in apoptosis resistance, and cisplatin was found to downregulate OCT4 protein expression in vitro . Ex vivo drug sensitivity analysis of HNSCC tumors confirmed the association between OCT4 expression and cisplatin sensitivity. Conclusion: This study introduces OCT4 immunohistochemistry as a simple and cost-effective diagnostic approach for clinical practice to identify HNSCC patients benefitting from radiosensitization by cisplatin using either full or reduced dosing.